Tualang Honey Protects the Rat Midbrain and Lung against Repeated Paraquat Exposure - Suk, Peng Tang; Nainamohamed Salam, Sirajudeen Kuttulebbai; Jaafar, Hasnan; Siew, Hua Gan; Muzaimi, Mustapha; Sulaiman, Siti Amrah (Hindawi Publishing Corporation, 2017)
Paraquat (PQ) is a dopaminergic neurotoxin and a well-known pneumotoxicant that exerts its toxic effect via oxidative stressmediated cellular injuries. This study investigated the protective effects of Tualang honey against PQ-induced toxicity in the midbrain and lungs of rats. The rats were orally treated with distilled water (2mL/kg/day), Tualang honey (1.0 g/kg/day), or ubiquinol (0.2 g/kg/day) throughout the experimental period. Two weeks after the respective treatments, the rats were injected intraperitoneally with saline (1 mL/kg/week) or PQ (10mg/kg/week) once per week for four consecutive weeks. After four weekly exposures to PQ, the glutathione peroxidase activity and the number of tyrosine-hydroxylase immunopositive neurons in the midbrain were significantly decreased in animals from group PQ (